Performance Based Evaluation of Cricothyroidotomy Simulators for Training. Issue 1 (October 2022) - Bliss, James P.; Etherton, Kent C.; Hodge, Douglas; Winner, Jennifer
The U.S. military has become increasingly reliant on simulators to train combat medical personnel. Human patient simulators that exist for training medical procedures represent task elements with varying degrees of fidelity. The goal of this research was to evaluate the functional fidelity of two commonly used simulators to train surgical cricothyroidotomy to experienced participants. Following a task analysis informed by experts, we collected performance training and test data from 14 experienced trainees. Each participant performed surgical cricothyroidotomies on porcine tracheas before and after five training sessions using one of two simulators. Comparisons of procedure completion times and errors showed development of task mastery by members of both training groups. Analyses of transfer of training from the final training session to the porcine posttest suggested that experienced participants were sensitive to differences between the training simulators and conditions of the posttest. Implications are presented as they relate to the use of simulation technologies for training cricothyroidotomy and the application of a standard method for fidelity assessment.